Impact of Marketing Information System on Product Performance in Nigerian Bottling Company Limited - Adeoti, Johnson O.; Olawale, Yinusa A.; Abolarinwa, Oladunni Olaife (NIU Journal of Social Sciences, 2017)
Many organizations fail to realize that the survival of their products in the competitive market is a function of their commitment to building and maintaining reliable marketing information system that is encompassing and embracing. This is because many companies in developing countries are often successful for a short period of time as they launched a new attractive product or an appealing service, but find it difficult to sustain over a longer period of time due to failure to continually gather information about the changes in market situation. Thus, this study examined the impact of marketing information system on product performance in the marketing department. The population of the study is the staff in the marketing department of the firm’s plant in kwara, Lagos and Oyo which consist of five hundred and twenty six (526) respondents. Data for the study were collected through administration of questionnaire to a randomly selected sample of 226 staff of Nigerian Bottling Company Plants. The data were analysed and hypotheses tested using regression analysis. The study revealed that marketing information system has significant effect on sales volume and that marketing information system has significant impact on product performance. The study concludes that company with effective and efficient marketing information system will develop competitive products that meet existing and potential buyers’ expectation in the market than organisation that do not have well organized and good marketing information system. Therefore, the study recommends that the company should develop and maintain advanced marketing information systems that provide company management with rapid and incredible information about consumers’ needs and wants, preferences and behaviour.